Pengaruh pendidikan kesehatan melalui short message service (sms) dan booklet tentang obesitas pada remaja overweight dan obesitas - Usi Lanita; Toto Sudargo; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2015)
Background: Adolescent is an important period to be considered because it is a transition period between children and adult. Nutrition problem in an adolescent is while the decline of physical activity, teenage generally have a big appetite, hence, they often look for additional food. The majority of diet that teenage like are an energy dense, sweet, and high-fat foods, which could have a risk of causing overweight and obesity if consumed excessively. Therefore, one of the efforts to overcome the nutrition problem is given a health education to teenage.Objective: To seek for the effect of health education by short message service (SMS) and a booklet about obesity on knowledge and body mass index (BMI) in an overweight and obese adolescent.Method: This study used a quasi-experiment with pre-test and post-test design. The subject were 105 respondents of overweight and obese senior high school students. The data were analyze used a paired t-test and ANOVA with p=0.05 and CI=95%.Results: Health education by SMS, booklet and the combination of SMS and booklet had a significant effect statistically (p<0.05) on knowledge in an overweight and obese adolescent. The combination of SMS and booklet had a significant effect statistically on BMI. The result of ANOVA in knowledge variable showed that combination of SMS and booklet group is more effective than other groups. Whereas health education of BMI variable by SMS, booklet, and the combination of SMS and booklet were not effective (p>0.05) to reduce BMI in an overweight and obese adolescent.Conclusion: Health education by SMS, booklet, and combination of SMS and booklet have an effect on increasing the knowledge in overweight and obese adolescent, whereas on BMI, only SMS and booklet have an effect on reducing BMI.